Quantitative Pupillometry as a Predictor of Pediatric Postoperative Opioid–Induced Respiratory Depression. (24th May 2021) - Packiasabapathy, Senthil; Zhang, Xue; Ding, Lili; Aruldhas, Blessed W.; Pawale, Dhanashri; Sadhasivam, Senthilkumar
Abstract : BACKGROUND: Safe postoperative pain relief with opioids is an unmet critical medical need in children. There is a lack of objective, noninvasive bedside tool to assess central nervous system (CNS) effects of intraoperative opioids. Proactive identification of children at risk for postoperative respiratory depression (RD) will help tailor analgesic therapy and significantly improve the safety of opioids in children. Quantitative pupillometry (QP) is a noninvasive, objective, and real-time tool for monitoring CNS effect-time relationship of opioids. This exploratory study aimed to determine the association of QP measures with postoperative RD, as well as to identify the best intraoperative QP measures predictive of postoperative RD in children. METHODS: After approval from the institutional review board and informed parental consent, in this prospective, observational study of 220 children undergoing tonsillectomy, QP measures were collected at 5 time points: awake preoperative baseline before anesthesia induction (at the time of enrollment [T1]), immediately after anesthesia induction before morphine administration (T2), 3 minutes after intraoperative morphine administration (T3), at the end of surgery (T4), and postoperatively when awake in postanesthesia recovery unit (PACU) (T5). Intraoperative use of opioid and incidence of postoperative RD were collected. Analyses were aimed at exploring correlations of QP measures with the incidence of RD and, if found significant, to develop a predictive model for postoperative RD. RESULTS: Perioperative QP measures of percentage pupil constriction (CONQ, P = .027), minimum pupillary diameter (MIN, P = .027), and maximum pupillary diameter (MAX, P = .034) differed significantly among children with and without postoperative RD. A predictive model including the minimum pupillary diameter 3 minutes after morphine administration (MIN3), minimum pupillary diameter normalized to baseline (MIN31), and percentage pupillary constriction after surgery (T4) standardized to baseline (T1) (CONQ41), along with the weight-based morphine dose performed the best to predict postoperative RD in children (area under the curve [AUC], 0.76). CONCLUSIONS: A model based on pre- and intraoperative pupillometry measures including CONQ, MIN, along with weight-based morphine dose-predicted postoperative RD in our cohort of children undergoing tonsillectomy. More studies with a larger sample size are required to validate this finding.